INCREASING STUDENTSâ€™ SPEAKING ABILITY USING SEQUENCED PICTURE STORY - Anggraini, Silvia; Rufinus, Albert; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research discussed about increasing Studentsâ€™ Speaking Ability Using Sequenced Pictures Story, A Classroom Action Research on the eighth grade Students of SMP Negeri 7 Pontianak in Academic Year 2017/2018. The focus was on pronunciation aspect. The research problem was â€œHow does Sequenced Pictures Story technique improve studentsâ€™ speaking ability of year-8 students of SMP Negeri 7 Pontianak Â in academic year 2017/2018?â€ In teaching-learning process, the participants were 25 students of VIII B class of which the teacher and the researcher was a collaborator. The result of this research showed that studentsâ€™ speaking ability, especially in pronunciation had increased. In first cycle, students had some problems in pronouncing words, and pause inappropriately, while in the second cycle, they had time to practice more, thus their problems were solved. In conclusion, Sequenced Pictures Story could be applied to increase studentsâ€™ speaking ability, especially pronunciation.Key words: Sequenced Pictures Story, Speaking Ability, Pronunciation